Tumbuh Kembang Nilai-nilai Keislaman di Kalangan Siswa-Siswi SMA di Surabaya Utara - Hartono, Hartono (ISLAMICA: Jurnal Studi Keislaman, 2010)
This paper discusses the highly controversial issues in the northern part of Surabaya; an issue that has attracted the attention of both parents and teachers alike, the issue of High School studentsâ attachment to the values of Islam. Many worried that given their attitude, these students have no concern whatsoever with the basic principles of Islam. This paper will show the otherwise by investigating carefully the notion of career choice among these students. This specific field of investigation has not received proportional attention from any field researcher apart from its significance both to the state of our education and moral conduct. The paper first argues that the attitude of these students is more complicated than many have assumed. It then tries to show that religious values are in fact the strongest determinants in students making their career choice. This theory comes as a serious challenge to many baseless assumptions that as a religion Islam has lost its influence over its younger followers. This research is done in different areas in the northern part of Surabaya. The questionnaires are distributed at random representing each area proportionally. The data are collected through these questionnaires based on the theory of Holland RIASEC.